ANALISIS SUPPLY CHAIN MANAGEMENT DI UMKM DESA SAMBIREJO - Ferrynela Purbo Laksono; Stephanus Eri Kusuma (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
ABSTRACTThis study aims to examine the business processes through the MSME supply chain, specifically in the chain of raw material access, production processes to marketing processes. The objects of this research focusing on five most developed MSME in Sambirejo Village, Ngawen, Gunung Kidul namely food, processed zinc, woven cloth, tile and local gabion. The business processes analyzed by using supply chain management approach. This study conducted a qualitative method based on interview and observation. Results of the study show that the pattern of MSME supply chains in Sambirejo Village is still relatively simple. In their processes, these MSME supply raw materials from suppliers or distributors of raw materials then process them. Afterwards, they distribute them to consumers using two different distribution methods (dual channel) there are distribute it directly and through an intermediary.Keywords: business process; UMKM; supply chain management